2023
DOI: 10.1158/1538-7445.am2023-5735
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5735: Novel KRAS G12D degrader ASP3082 demonstrates in vivo, dose-dependent KRAS degradation, KRAS pathway inhibition, and antitumor efficacy in multiple KRAS G12D-mutated cancer models

Abstract: KRAS is one of the most frequently mutated oncogenes in various cancers. Among KRAS mutations, KRAS G12D is the most frequent driver mutation and is found in approximately 34% of patients with pancreatic ductal adenocarcinoma (PDAC), 12% of patients with colorectal cancer (CRC), 4% of patients with lung adenocarcinoma, and in a subset of patients with other solid tumors. We have identified ASP3082 as a novel KRAS G12D degrader with high potency and selectivity. Here, we have evaluated in vivo antitumor activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…ASP3082 is a protein degrader that connects mutated KRAS G12D with E3 ligase to initiate the degradation process through ubiquitination. An in vivo study demonstrated its anti-tumor efficacy in PDAC, CRC, and NSCLC models ( 97 ). A phase I trial of ASP3082 is currently ongoing (NCT05382559).…”
Section: Discussionmentioning
confidence: 99%
“…ASP3082 is a protein degrader that connects mutated KRAS G12D with E3 ligase to initiate the degradation process through ubiquitination. An in vivo study demonstrated its anti-tumor efficacy in PDAC, CRC, and NSCLC models ( 97 ). A phase I trial of ASP3082 is currently ongoing (NCT05382559).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of the PROTAC to both molecules targets the protein of interest to ubiquitination and subsequent degradation by the ubiquitin-proteasome system. ASP3082 (Astellas Pharma) is a degrader that binds to both KRAS G12D and E3 ubiquitin ligase, fostering KRAS G12D degradation [125]. Preclinical data suggest significant activity against pancreatic cancer in xenograft mouse models of PDAC.…”
Section: Allele Specific Ras Inhibitors G12c Inhibitorsmentioning
confidence: 99%